Institutional China and Chinese OFDI - Buckley, Peter J. (Henry Stewart Talks, 2014)
Outward Foreign Direct Investment from China: scale and scope, China FDI inward and outward, Location aspects of Chinese OFDI, Institutional drivers in China, China’s multinationals, Foreign takeovers, Strategy of Chinese firms, Is Chinese ODI a special case?, Emerging trends, Main administrative actors in China, The OFDI approval process in China, From prohibition to liberalisation, Special cases 1: Africa, Special cases 2, Chinese FDI in tax havens, Microeconomic context